PROFESSIONAL TRAINING OF ECONOMIC INDUSTRY PROFESSIONALS IN THE UKRAINIAN AND POLISH EDUCATIONAL SPACE: BASIC CONCEPTS - Alla Zagorodnia (National Academy of Educational Sciences of Ukraine, 2019)
The article compares the basic notions of professional training economic sector in the Ukrainian and Polish educational space. The author argues that Ukraine's entry into the global and European educational space needs studying foreign experience of training future professionals chosen field. The author draws on the achievements of comparative education for parallels in the study of basic concepts in the Ukrainian and Polish educational space. Under the current socio-economic conditions contradictions between the content of educational and economic needs of the changing economic and social development in the sphere of high technology and information technology, between the level of professional economic education and employment opportunities for young professionals become more apparent. Excellent for the late 20th and early 21st century, changes in the nature of education, i.e. in its orientation, for purposes sense, increasingly orient it to the free development rights on creativity, independence students, competitiveness, mobility of future specialists. Modern higher education provides for the fundamental, general cultural, practical and professional training that should determine the pace and level of scientific, technical, economic and socio-cultural process, and formation of the intellectual potential of society. The analyzed concepts allow to conclude that there are different approaches to their interpretation, which often complement each other, sometimes - contrary to that but makes it possible to assert the common aspects and related areas of research training of future specialists of economic direction in terms of higher educational institutions of Ukraine and Poland.